Forced Leadership as a Social Psychological Phenomenon in Professionally Successful Women Scientists (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
In today's world, women are increasingly taking the place of leaders, so they have to be active, focused, resistant to stress, have a high level of self-regulation, and be able to work in a team. So, we can see how women are sometimes forced to become leaders in difficult life circumstances. Due to persistence, self-education, determination, they work in leadership positions and demonstrate masculine personality traits. The study aimed to study the psychological characteristics of women scientists who hold high positions in educational establishments - vice-rector, dean, and department head. We hypothesized that the professional success of women scientists depends on the level of their potential leadership skills. The study involved 75 women from higher education institutions who successfully work as vice-rectors, deans, heads of departments. All of them have the degree of doctors of philosophy from various scientific fields and combined scientific activity with managerial activity. Analysis of the results of empirical research showed that a high level of leadership skills determines the professional success of 37% of women studied, but 63% of women scientists have other determinants of professional success. Differences in indicators were identified, and three groups of women were characterized depending on the level of development of their leadership abilities. In groups of women with a medium and low level of leadership skills, the main determinants of professional success are the focus on real-life circumstances, high level of development of stable emotional and volitional sphere, voluntary self-regulation, self-control in difficult situations, emotional stability. Women who have achieved professional success, not on the basis of potential leadership abilities, form a socially determined personal quality - forced leadership, which we tend to consider as a social psychological phenomenon, which is based on the ability to adapt to living conditions in situations requiring a person to choose against own individual psychological features, namely to become a leader, to cultivate the traits inherent in a true leader.